2021
DOI: 10.3389/fbioe.2021.760179
|View full text |Cite
|
Sign up to set email alerts
|

Early Efficacy of Type I Collagen-Based Matrix-Assisted Autologous Chondrocyte Transplantation for the Treatment of Articular Cartilage Lesions

Abstract: Background: Articular cartilage is a complex structure that allows for low frictional gliding and effective shock absorption. Various sports injuries and inflammatory conditions can lead to lesions in the articular cartilage, which has limited regenerative potential. Type I collagen combined with autologous chondrocytes in a three-dimensional culture were used to induce the regeneration of single-layer autologous expanded chondrocytes without chondrogenic differentiation.Purpose: To assess the clinical, radiol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 24 publications
(24 reference statements)
0
5
0
2
Order By: Relevance
“…Thus, PBA moieties could enhance the formation of chondrocyte clusters by promoting the formation of cell filopodia, which promoted cell–cell contacts and favored cartilage differentiation. [ 36 ] Cells with filopodia had higher adhesion strength than those without filopodia. [ 37 ] Therefore, the chondrocytes on the AHAMA‐PBA hydrogel surfaces were able to bond tightly to the interface by forming multiple filopodia.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, PBA moieties could enhance the formation of chondrocyte clusters by promoting the formation of cell filopodia, which promoted cell–cell contacts and favored cartilage differentiation. [ 36 ] Cells with filopodia had higher adhesion strength than those without filopodia. [ 37 ] Therefore, the chondrocytes on the AHAMA‐PBA hydrogel surfaces were able to bond tightly to the interface by forming multiple filopodia.…”
Section: Discussionmentioning
confidence: 99%
“…In a phase I–II trial T 2 reductions upon intra-articular administration of ex vivo expanded autologous mesenchymal stromal cells indicated cartilage regeneration ( Soler et al, 2016 ). Three recent studies demonstrated T 2 reductions after implanting a biomaterial scaffold seeded with chondrocytes ( Li et al, 2021 ; Xu et al, 2021 ; Janacova et al, 2022 ). In two of the studies early efficacy suggesting cartilage repair translated into cartilage T 2 reductions within 3–6 months of implantation, accompanied by improvements in functionality and pain levels ( Li et al, 2021 ; Xu et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Three recent studies demonstrated T 2 reductions after implanting a biomaterial scaffold seeded with chondrocytes ( Li et al, 2021 ; Xu et al, 2021 ; Janacova et al, 2022 ). In two of the studies early efficacy suggesting cartilage repair translated into cartilage T 2 reductions within 3–6 months of implantation, accompanied by improvements in functionality and pain levels ( Li et al, 2021 ; Xu et al, 2021 ). Texture analysis of T 2 quantitative maps has also been introduced to study cartilage repair ( Janacova et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…В настоящее время часто используют мембраны на основе гиалуроновой, полигликолиевой кислот, агарозы и альгината, а также различных полимеров, которые могут быть представлены в виде волокон, сетки или гелей [5,6].…”
unclassified
“…Так же как ACI, методика предполагает двухэтапное хирургическое вмешательство. Однако, в отличие от них, в MACI после культивирования АХ засевали на какой-либо скаффолд (трехмерную матрицу) и культивировали еще в течение 3 дней, а затем имплантировали в область дефекта [5,6]. Было показано, что трехмерная структура матриц способствует поддержанию дифференцированного фенотипа хондроцитов и правильному распределению их в дефекте [11,12].…”
unclassified